A Possible Role of the Aleurone Expressed Gene HvMAN1 in the Hydrolysis of the Cell Wall Mannans of the Starchy Endosperm in Germinating Hordeum vulgare L. Seeds - Iglesias-Fernández, Raquel; Pastor-Mora, Elena; Vicente-Carbajosa, Jesús; Carbonero, Pilar (Frontiers in Plant Science, 2020)
The barley endo--mannanase (MAN) gene family (HvMAN1-6) has been identified and the expression of its members analysed throughout different plant organs, and upon seed development and germination. The HvMAN1 gene has been found to be highly expressed in developing and germinating seeds. The MAN (EC 3.2.1.78) enzymatic activity gets a maximum in seeds at 48 h of germination (post-germination event). Immunolocalization of mannan polymers in seeds has revealed the presence of these polysaccharides in the endosperm cell walls (CWs). By mRNA in situ hybridization assays, the HvMAN1 transcripts have been localized to the aleurone layer, but not to the dead starchy endosperm cells. These data suggest that MAN1 is synthesized in the aleurone layer during early seed imbibition and moves potentially through the apoplast to the endosperm where the hydrolysis of the mannan polymers takes place after germination sensu stricto. Hence, mannans in the starchy endosperm CWs, besides their structural function, could be used as reserve compounds upon barley post-germination.